A Beginner's Guide to Water Management—Nutrients - Florida LAKEWATCH; Mark Hoyer (EDIS)
Nutrients are substances required by all organisms for growth, and they are found in every aquatic system. Nutrients are also the object of much discussion by lake management professionals and the general public who are concerned about the influence nutrients sometimes have on the growth of algae and/or aquatic plants in lakes. Written for the lay public, this information circular is an ideal reference booklet for students and/or professionals interested in water management. First published Aug. 2000.